PENGARUH NILAI, TINGKAT PENGETAHUAN, DAN SIKAP TERHADAP PERENCANAAN KEUANGAN HARI TUA - Astuti, Ririn Nindia; Hartoyo, Hartoyo (Jurnal Ilmu Keluarga dan Konsumen, 2013)
This study aimed to analyze the correlation between attitudes, subjective norms, and behavioral control in financial retirement planning. In addition, this study also aimed to analyze the influence of student characteristics, family characteristics, values, knowledge, attitudes, subjective norms, and behavioral control on the intention to do financial retirement planning that was approached by Theory of Planned Behaviour. The study involved 250 undergraduate students of Bogor Agricultural University who took management of financial consumer courses. Value was measured by Multi Item Measures of Values (MILOV). Data were collected by self-report techniques and was analyzed by hierarchical cluster analysis, Pearson correlation test, and logistic regression test. The results showed that attitudes, subjective norms, and behavioral control correlated positive significantly with the intention to do financial retirement planning. In addition, the intention to do financial retirement planning was influenced by age, father’s income, the value (the value’s orientation was low on a sense of accomplishment dimension and self-respect dimension; high on security dimension and self-fulfilment dimension), knowledge, and attitudes.